2014
DOI: 10.3109/10428194.2013.847934
|View full text |Cite
|
Sign up to set email alerts
|

Impact of mutations inFLT3, PTPN11andRASgenes on the overall survival of pediatric B cell precursor acute lymphoblastic leukemia in Brazil

Abstract: We analyzed mutations in four genes (FLT3, KRAS/NRAS and PTPN11) that might disrupt the RAS/mitogen activated protein kinase (MAPKinase) signaling pathway, to evaluate their prognostic value in children younger than 16 years old with B-cell precursor acute lymphoblastic leukemia (Bcp-ALL). The overall survival (OS) was determined with the Kaplan-Meier method. MAPKinase genes were mutated in 25.4% and 20.1% of childhood and infant Bcp-ALL, respectively. Children with hyperdiploidy were more prone to harboring a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 35 publications
1
14
2
1
Order By: Relevance
“…Barbosa et al. reported that 15.8% (3/19) of hyperdiploid (defined by DNA index of ≥1.16) ALL displayed PTPN11 mutations, whereas the frequency was 3.4% (two of 59) in patients with nonhyperdiploid ALL . In our study, PTPN11 mutations occurred in 3.0% (16/526) of all pediatric B‐precursor ALL and 3.4% (2/59) of hyperdiploid ALL.…”
Section: Discussionmentioning
confidence: 39%
See 3 more Smart Citations
“…Barbosa et al. reported that 15.8% (3/19) of hyperdiploid (defined by DNA index of ≥1.16) ALL displayed PTPN11 mutations, whereas the frequency was 3.4% (two of 59) in patients with nonhyperdiploid ALL . In our study, PTPN11 mutations occurred in 3.0% (16/526) of all pediatric B‐precursor ALL and 3.4% (2/59) of hyperdiploid ALL.…”
Section: Discussionmentioning
confidence: 39%
“…In our study, PTPN11 mutations occurred in 3.0% (16/526) of all pediatric B‐precursor ALL and 3.4% (2/59) of hyperdiploid ALL. The frequency of PTPN11 mutations was much lower than that reported from the small Brazilian series and a large cohort from Italy . The definition of hyperdiploidy was different among these studies; we used karyotyping to identify hyperdiploid ALL with a chromosomal number of 51–68, whereas the previous studies used DNA index by flow cytometry.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Risk‐based therapy is emphasized in therapeutic protocols for paediatric ALL to reduce the toxicity in patients with low risk and provide aggressive therapies for those with high risk. Age, initial white blood cells, ALL subtype, chromosomal aberrations, or MRD have been considered in the risk stratification, although the exact disease‐specific and sensitive biomarkers remain unknown . Proteomics is an opening and new window to make the discovery and identification of protein‐based biomarkers possible in paediatric ALL‐relapses, and a useful tool to develop individual and personalized therapies .…”
Section: Introductionmentioning
confidence: 99%